Study guides

☆☆

Q: How do you solve for x when a plus x equals b?

Write your answer...

Submit

Still have questions?

Related questions

y-b/x=m

How do you solve 4y plus x equals 8

in order to solve this problem you have to solve for x first wich you are given the data to pre forme so x=4 and x.2=8 and 8=y and y-4=4=a=x so a+8=12 and 12=b

y=b+x+x^2 This is a quadratic equation. The graph is a parabola. The quadratic equation formula or factoring can be used to solve this.

Can you help with this equation? Thanks. Solve for x and y and z for the following. x plus y plus z equals 9 x plus 2y plus 3z equals 23 x plus 5y plus -3z equals -7

X +13 equals 22, X equals nine

you can not solve this equation

The equation does not have a solution.

the answer is: (y-b)/x = m y = mx + b y - b = mx (y-b)/x = m

Y equals 1 and X equals 1

Your two equations are: AX + BY = A - B BX - AY = A + B + B Because you have four variables (A, B, X, Y), you cannot solve for numerical values for X and Y. There are a total of four answers to this question, solving each equation for X and Y independently. First equation: X = (A - B - BY)/A Y= (A - B - AX)/B Second equation: X = (A +2B +AY)/B Y = (BX - A - 2B)/A

7

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

7.5

If y = mx + b, then x = (y-b)/m (for m not equal to zero).

To solve for x, we'd have to know what this expression equals.

X = 1.8

x= -.5

The answer is x = 2.

x=-2

x = -8

x = 5, y = -1

X= (b-c)/a

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0

x = 3 and y = 3 Form a simultaneous equation and solve by elimination.